Public Policy Analysis on the Required Administration of Mountainous Areas in Turkey - Karaman, Zerrin Toprak (Advances in Social Sciences Research Journal, 2024)
Turkey is a mountainous country. 50% of Turkey's territory is located at an altitude of 1000 meters and 2/3 of it is located at an altitude of 500 meters and above. The percentage of mountainous areas in the total of Turkish lands is 74.6%. How aware is the administration of the mountains that bring multi-faceted and strategic meaning to the geographical structure of Turkey? Mountains need to be subjects of public policies. Yet they have not been regulated by law so far. What are the reasons behind this? Human beings must first design the spatial environment in which they live. This principle should be linked to the need for an effective administration planning of mountains. However, unfortunately even the word "mountain" does not clearly appear in the public policies of our country. These policies only focus on resources that are categorized as above-ground and underground. Administrative strategy of mountainous areas is not included in space analyses. It is also a security policy requirement to create basic public policies around the mountain in a multifaceted way, not by hiding mountain area administration under the title of any natural resource, but by handling it separately so that it is obvious within the goals of sustainable community development. Due to the characteristics of the mountains, international interest in the subject is also gradually increasing. 11th of December has been annually celebrated as the “International Mountain Day” since 2002. The ecological resilience of nature related to the existence of valuable resources also corresponds to the resilience of societies against all kinds of threats, especially against climate changes. The world now evaluates countries in terms of how they can manage these resources not just in terms of which goods and resources they have. It is important to make a distinction between the administration of mountainous areas within the public administration organization and the rural activities and to highlight the uniqueness of this type of administration. Public policies on mountains and administration of mountainous areas should rapidly be established in Turkey. In order to find balance between usage and protection, it is crucial to utilize the skills of developing scientific design strategies, objectively analyzing and interpreting and switching to new organizations and methods that are up-to-date. This paper focuses on the need for creating public policies regarding mountainous areas and proposes a model for these policies.